Effect-based assessment of toxicity removal during wastewater treatment. (1st December 2017) - Välitalo, Pia; Massei, Riccardo; Heiskanen, Ilse; Behnisch, Peter; Brack, Werner; Tindall, Andrew J.; Du Pasquier, David; Küster, Eberhard; Mikola, Anna; Schulze, Tobias; Sillanpää, Markus
Abstract: Wastewaters contain complex mixtures of chemicals, which can cause adverse toxic effects in the receiving environment. In the present study, the toxicity removal during wastewater treatment at seven municipal wastewater treatment plants (WWTPs) was investigated using an effect-based approach. A battery of eight bioassays was applied comprising of cytotoxicity, genotoxicity, endocrine disruption and fish embryo toxicity assays. Human cell-based CALUX assays, transgenic larval models and the fish embryo toxicity test were particularly sensitive to WWTP effluents. The results indicate that most effects were significantly reduced or completely removed during wastewater treatment (76–100%), while embryo toxicity, estrogenic activity and thyroid disruption were still detectable in the effluents suggesting that some harmful substances remain after treatment. The responsiveness of the bioassays was compared and the human cell-based CALUX assays showed highest responsiveness in the samples. Additionally, the fish embryo toxicity test and the transgenic larval models for endocrine disrupting effects showed high responsiveness at low sample concentrations in nearly all of the effluent samples. The results showed a similar effect pattern among all WWTPs investigated, indicating that the wastewater composition could be rather similar at different locations. There were no considerable differences in the toxicity removal efficiencies of the treatment plants and no correlation was observed with WWTP characteristics, such as process configuration or sludge age. This study demonstrated that a biotest battery comprising of multiple endpoints can serve as a powerful tool when assessing water quality or water treatment efficiency in a holistic manner. Rather than analyzing the concentrations of a few selected chemicals, bioassays can be used to complement traditional methods of monitoring in the future by assessing sum-parameter based effects, such as mixture effects, and tackling chemicals that are present at concentrations below chemical analytical detection limits. Graphical abstract: Image 1 Highlights: Toxicity removal during wastewater treatment at 7 municipal WWTPs was investigated. Removal efficiency was assessed by an effect-based approach comprising of multiple endpoints. Large volumes of influent and effluent samples were extracted with a novel device. Embryo toxicity, estrogenic activity and thyroid disruption were detected in effluent samples. The results showed a similar effect pattern among all the WWTPs.